Mastery of Soft Skills Through Co-curricular Uniform Body - Ismail, Fadillah (Journal of Social Transformation and Regional Development, 2021)
Involvement students in the co-curricular of uniformed bodies are one of the significant alternatives in the effort to apply elements of soft skills among students in IPT. This study is a longitudinal survey study aimed at measuring the level of mastery of soft skills among 912 students who took a uniformed body co-curriculum course. There are seven attributes of insanity skill (soft skill) for IPT students as outlined by the Ministry of Higher Education Malaysia (KPTM) including communication skills, leadership, teamwork, critical thinking and problem solving, lifelong learning, entrepreneurship, and professional moral ethics skills (KPT 2006) applied. Statistical Package for Social Science Version 20 software was used to analyze the findings of this study. The results show that there is a change in the mastery of the seven soft skills among students before and after joining the uniformed body.